Analysis Of The Influence Of Motivation, Work Discipline And Commitment On The Performance Of Civil Servants With Competence As An Intervening Variable At The Center For The Implementation Of Agricultural Instrument Standards North Sumatra - Zainal; Sri Rahayu (Yayasan Multidimensi Kreatif, 2024)
This study aims to determine and analyze the effect of motivation, work discipline and commitment on the performance of Civil Servants with competence as an intervening variable at the North Sumatra Agricultural Instrument Standards Application Center. The population in this study was 110 employees. The number of samples taken was 86 respondents. The sampling technique used was saturated sampling. This study uses quantitative primary data collected through questionnaires and processed with the Smart-PLS Software application. The study was conducted in 2024. The analysis technique used the path analysis model. Based on the results of the study, it can be concluded that: Work Discipline (X2) has a positive effect on Performance (Y), with a path coefficient value (Original Sample column) of 0.088, and a P-Values value = 0.006. Work Discipline (X2) has a positive effect on Competence (Z), with a path coefficient value (Original Sample column) of 0.091, and a P-Value = 0. Commitment (X3) has a positive effect on Performance (Y), with a path coefficient value (Original Sample column) of 0.412, and a P-Value = 0. Commitment (X3) has a positive effect on Competence (Z), with a path coefficient value (Original Sample column) of 0.531, and is significant with a P-Value = 0. Competence (Z) has a positive effect on Performance (Y), with a path coefficient value (Original Sample column) of 0.219, and a P-Value = 0.018. Motivation (X1) has a positive effect on Work Spirit (Z), with a path coefficient value (Original Sample column) of 0.291, and a P-Value = 0, Motivation (X1) has a positive effect on Performance (Y), with a path coefficient value (Original Sample column) of 0.379, and has an effect on the P-Value = 0. The magnitude of the parameter coefficient for the work discipline variable (X2) on Performance (Y) through competence (Z) is 0.02, which means that there is a positive indirect effect of work discipline (X2) on performance (Y) through competence (Z) or it can be interpreted that the higher the value of work discipline (X2), the performance (Y) through competence (Z) is 2%. The magnitude of the parameter coefficient for the commitment variable (X3) on Performance (Y) through competence (Z) is 0.116, which means that there is a positive indirect influence of commitment (X3) on performance (Y) through competence (Z) or it can be interpreted that the higher the commitment value (X3), the performance (Y) through competence (Z) is 11.6%. The magnitude of the parameter coefficient for the motivation variable (X1) on Performance (Y) through competence (Z) is 0.083, which means that there is a positive indirect influence of motivation (X1) on performance (Y) through competence (Z) or it can be interpreted that the higher the motivation value (X1), the performance (Y) through competence (Z) is 8.3%.